Understanding conflict and conflict analysis - Jeong, Ho-Won. (Los Angeles : SAGE Publications Inc, 2008)
. Effectively fills a long-standing void and will no doubt be hailed as a much-needed new addition to the literature. This text very much exemplifies the strength of Ho-Won Jeong as a theorist and one of the more prolific writers in the larger peace and conflict studies field. the final three chapters on 'De-escalation Dynamics' (which includes a brief section on third party intervention), on 'Conciliation Strategies, ' and especially the one on 'Ending Conflict, ' which provides a range of outcomes beyond the usual focus on third party intervention (read mediation) epitomizes the value of thi.
PART I: Concepts and analysis. Approaches to understanding conflict -- Conflict analysis framework -- -- PART II: Sources and situations. Sources of conflict -- Conflict situations and behaviour -- -- PART III: Process and structure. Process of conflict -- Interlinkage and context -- -- PART IV: Dynamics and escalation. A system of conflict dynamics -- Escalation and entrapment -- -- PART V: De-escalation and termination. De-escalation dynamics -- Conciliation strategies -- Ending conflict.
Includes bibliographical references (p. [245]-255) and index.
Keywords: Social conflict; Conflict management; Conflict (Psychology); Electronic books